2013
DOI: 10.1002/jsfa.6127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary nutrient density and vitamin premix withdrawal on performance and meat quality of broiler chickens

Abstract: Increasing dietary nutrient density improved broiler performance but impaired meat quality while vitamin premix withdrawal during finisher periods had no negative effect on broiler performance and meat quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 43 publications
(98 reference statements)
1
10
0
1
Order By: Relevance
“…The LND vs HND diet contained less energy and nutrients by one percent point of crude protein (CP), 50 kcal of nitrogen-corrected true metabolizable energy, 0.05 percent point of available phosphate, and 0.05 percent point of lysine. These nutrient reduction can be considered moderate as compared with the previous studies ( Brickett et al, 2007 ; Zhao et al, 2009 ; Li et al, 2010 ; Mirshekar et al, 2013 ), in which the LND vs HND diet was formulated to reduce CP levels by 2 percent points, and energy levels by more than 150 kcal/kg of diet. Diet and water were provided ad libitum .…”
Section: Methodsmentioning
confidence: 84%
“…The LND vs HND diet contained less energy and nutrients by one percent point of crude protein (CP), 50 kcal of nitrogen-corrected true metabolizable energy, 0.05 percent point of available phosphate, and 0.05 percent point of lysine. These nutrient reduction can be considered moderate as compared with the previous studies ( Brickett et al, 2007 ; Zhao et al, 2009 ; Li et al, 2010 ; Mirshekar et al, 2013 ), in which the LND vs HND diet was formulated to reduce CP levels by 2 percent points, and energy levels by more than 150 kcal/kg of diet. Diet and water were provided ad libitum .…”
Section: Methodsmentioning
confidence: 84%
“…Birds were weighed and feed intake was measured weekly. At 42 days of age, following 6 h fasting, chickens were weighed and then slaughtered by cervical dislocation . First of all, liver samples were removed immediately.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of vitamin level in poultry diets on performance remains controversial. Khajali, Khoshoei, and Moghaddam (2007) reported that removing vitamin from broiler diets from 28 to 49 days of age had a little impact on growth performance, the same point was supported by Mirshekar, Dastar, Shabanpour, and Hassani (2013), in which vitamin withdrawal has no significant effect on 42-day broiler's body weight. Results from the growth performance were similar to those observed by Moravej, Alahyari-Shahrasb, Kiani, Bagherirad, and Shivazad (2013), in that broiler chickens fed five treatment groups (basal diet 0, 33%, 66%, 100%…”
Section: Discussionmentioning
confidence: 82%